Longitudinal influences of adverse childhood experience patterns on mental health among older Chinese people - Yue Zeng; Renhui Lyu (BMC Geriatrics)
Abstract Background Childhood experiences have been shown to affect mental health in later life. However, the relationships between childhood adversity patterns and mental health trajectories in later life have not been fully examined. Using a pattern-based approach, this research identified distinct patterns of exposure to adverse childhood experiences (ACEs) and longitudinal relationships between ACE patterns and mental health trajectories among older Chinese people. Methods Using data on 4,343 respondents aged 60 or older from four waves of the China Health and Retirement Longitudinal Study (2011, 2013, 2015, and 2018) and a 2014 life history survey, latent class analysis was employed to identify patterns of ACEs. Parallel process latent growth curve models were applied to examine the longitudinal relationships between ACE patterns and depressive symptoms and cognitive function. Results Three meaningful patterns of ACE emerged: Low ACEs, Polyvictimization, and Absence of parental care. ACE patterns were associated with the trajectory of cognitive function but not depression, and the effects were particularly evident in the Polyvictimization class. Conclusions This study emphasizes the significant influences of ACE patterns on cognition in later life. Additionally, early screening, prevention, assessment, and interventions for people with polyvictimization experiences are critical for alleviating or delaying cognitive decline in later life.